The Californios : a history, 1769-1890 - Janin, Hunt, 1940-; Carlson, Ursula, 1943- (McFarland & Company, Inc., Publishers, 2017)
"Before the Gold Rush of 1848-1858, Alta (Upper) California was an isolated cattle frontier--and home to a colorful group of Spanish speaking, non-indigenous people known as Californios. Many traces of their culture remain in California. Drawing on firsthand contemporary accounts, the authors chronicle the rise and fall of Californio men and women"-- Provided by publisher.
Keywords: Frontier and pioneer life -- California.; California -- History -- To 1846.; California -- Ethnic relations.; California -- History -- 19th century.; Spain -- Colonies -- America -- History.; Californie -- Histoire -- Jusqu'à 1846.; Californie -- Histoire -- 19e siècle.; Espagne -- Colonies -- Amérique -- Histoire.; HISTORY -- United States -- State & Local -- General.; Frontier and pioneer life; Spanish colonies; America; California; To 1899; History